ANALISIS PENDAPATAN UKM (STUDI KASUS PADA USAHA OBAT PERTANIAN DI KOTA BANJARBARU) TAHUN 2022 - Amalia, Cahya; Suripto, Suripto (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Indonesia, as an archipelagic country with a large population, urgently needs the role of SMEs to facilitate socio-economic relations between communities. SMEs play an important role in Indonesia's economic progress, including in the agricultural sector. Agricultural SMEs assist fruit and vegetable farmers in their work, and contribute significantly to national GDP, employment, and food supply. This study uses a quantitative descriptive method with a survey/observation strategy in Banjarbaru City, South Kalimantan. The purpose of the study is to measure the decrease in the income of SMEs in the agricultural sector. The results of the study show that capital, labor, and business duration have a positive and significant effect on the income level of agricultural drug business actors in Banjarbaru.